The Impact of Culture on Organizational Performance in Selected Textile Firms in Nigeria (Nordic Journal of African Studies, 2003)
The present study examines the multidimensional impact of culture on organizational performance in selected textile firm from Lagos, Asaba and Kano in Nigeria. The main objectives of the study were to (i) identify the cultural variables which influence organizational performance (ii) determine the nature of the relationship between culture and performance (iii) identify other determinants of performance and (iv) determine the ways in which culture interact with other factors to influence organizational performance.The data were collected using both qualitative and quantitative methodologies. The former were collected through interviews and observations while the latter were collected via structured questionnaire and from documents. In all, 630 respondents were used for the study. The respondents were selected using multiple sampling techniques - comprising of (i) stratified random sampling (ii) quota sampling and (iii) systematic sampling techniques. The data were analysed using parametric and non-parametric statistics.The main finding of the study was that irrespective of their cultural backgrounds, workers in the textile industry appeared to have imbibed the industrial way of life. The results of the analysis of the cultural variables showed a high level of commitment to work, low level of labour turnover and absenteeism, positive beliefs about work, positive work values, attitudes, and norms in all the firms studied. But these positive attributes of the cultural variables did not translate directly to high level of organizational performance in these mills because some other variables were at work. This was an indication that culture was not the sole determinant of organizational performance. Other factors most especially exogenous variables such as the economy, technology and the murky political climate all influence organizational performance significantly and much more than endogenous variable such as size, structure, and style of management.In the main the study showed that there was a significantly positive relationship between culture and organizational performance. This notwithstanding, the study also found that the selected firms were not performing very well because of some peculiar problems. These included the problem of the inadequacy of technology and social infrastructures most especially electricity and the incessant fuel crisis. Coupled with this was the problem of low effective demand for domestic prints and the preference of the average Nigerian for imported wax. Low level of effective demand had also meant low level of capacity utilization that prevented these mills form making profits. Moreover, there was the problem associated with the globalization and liberalization of trade and the impact of the murky political climate most especially in the years between 1993 and 19998. The study concluded on the note that organizational performance is a multi -dimensional phenomenon as it largely depended on the contingencies confronting a particular organization.